The physical properties and stability of purple yam (Ipomoea batatas (L.) Lam ) lipstick - Susmiatun, Susmiatun; kusuma, Anjar mahardian; Budiman, Arif; Hapsari, Indri (Universitas Ahmad Dahlan, 2018)
The purple yam (Ipomoea batatas (L) Lam) has a useful anthocyanin as a natural dye which safer compare to the synthetic dyes. Anthocyanins have the antioxidant effect that can capture free radicals. The purpose of this study was to assess the effect of purple yam extract in various concentrations on the physical properties and physical stability of lipstick. Lipstick was made in three formulas that is L01, L02, L03. To evaluate the quality of the product, the physical properties, and stability test for purple yam lipsticks were conducted. Physical properties test consisted of organoleptic tests, melting point test, hardness test, homogeneity test, the Pap test, and pH test. Lipstick stability tests were performed by stored lipstick for 30 days at room temperature 25 Â°C, then observed the change of shape, color, and odor during storage. â€œWâ€ a top market leader lipstick in Indonesia was used as a control. Observed data of melting point, strength, and pH of lipstick were analyzed using One Way ANOVA and continued with Tukey. Organoleptic data, homogeneity, topicality and lipstick stability were described descriptively. The results showing no significant differences between lipstick L01, L02, L03 in organoleptic, homogeneity, pH and lipstick physical stability. However, when comparing with W lipstick, there is a significant difference in the melting, hardness and smearing points between L01, L02, L03 lipstick with W lipstick. It was concluded that purple yam extract may influence the physical properties of lipstick in particular melting point and hardness of lipstick. Although it has no effect on the stability of purple yum lipstick.